Digital image correlation : from integer pixel to sub-pixel - Wicaksono, Anjar Puji. (2011)
In collaboration with the advancement of computer technology and digital image acquisition (digital imaging), Digital Image Correlation (DIC) technique is getting more common in analyzing strain/deformation on the surface.